Impact of Glass Ceiling on Mental Health Status among Private Sector’s Working Women - Bibi Fatima; Dr. Mahreen Siddiqui; Dr. Samreena Rose (Research Journal of Psychology, 2025)
Persistent Glass Ceiling effect in organizational hierarchies has become a significant barrier for women, particularly in the private sectors. Purpose of the study was to investigates that how systemic barriers of career advancement affect psychological well-being of working women. Objectives of the study explore the impact of glass ceiling issues on mental health status of working women in private organizations. Using a sample of 150 female employees from various private organizations with age of 35 to 55 Mean = 1.40 Sd= .492. Measures were applied for data collection a) Demographic information form b) Glass Ceiling Scale (GCS), developed by Hameed and Gul-e-Rana (2005) c) Scale of mental health was developed by Sofia Tabassam (1997). Correlation method multiple regression analysis was applied to calculate the relationship between glass ceiling and mental health. Findings of the study indicate a strong correlation between glass ceiling and mental health, which indicates that women were reporting higher levels of stress, anxiety, and job dissatisfaction.